The Effect of Time Token Strategy on Students Reading Comprehension - Oktifa Tisnasari; Putry Asilestari; Wida Rianti (FKIP - Universitas Pahlawan Tuanku Tambusai, 2024)
This experimental research was carried out at SMP IT Bangkinang. This research was conducted to determine the effect of the Time token strategy on students' reading comprehension. This research methodology uses a quasi-experimental design. The sample for this research was students from class VIII F as the control class and VIII E as the experimental class. The experimental class consists of 30 students and the control class consists of 30 students. This study used a purposive sampling technique in which the researcher chose the class category to be examined. The instrument used in this research was a reading comprehension test which consisted of 20 multiple choice questions. Data were analyzed using the SPSS 16 program. Based on research data analysis, the average student score on the pre-test was 70.50 and 87.83 on the post-test. Data analysis shows significance (2-tailed) 0.000<0.05, which means Ha is accepted. It can be concluded that there is an influence of the Time token strategy on the reading comprehension of class VIII SMP IT Bangkinang students.